1995
DOI: 10.1159/000188353
|View full text |Cite
|
Sign up to set email alerts
|

Serum Lipoprotein (a) Levels in Patients with Chronic Renal Failure – Evolution after Renal Transplantation and Relationship with Other Parameters of Lipoprotein Metabolism: A Prospective Study

Abstract: In order to analyze the relationship between lipoprotein (a) [Lp (a)] and other lipoproteins during chronic renal failure and once renal function is restored after kidney transplantation, we determined the serum levels of total lipoprotein, high-density lipoprotein, low-density lipoprotein, and very-low-density lipoprotein cholesterols, total and very-low-density lipoprotein triglycerides, apohpoproteins A-I, B, C-II, C-III, and E, and E, and Lp (a) in 30 patients with chronic renal failure before and 12 month… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

1996
1996
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 4 publications
1
7
0
Order By: Relevance
“…There is frequently a reduction in blood pressure posttransplantation mirroring the central blood pressure regulatory role of the kidney, but also contributing is the increased use of vasoactive agents. Improvement in lipid parameters also follows restoration of normal renal function post-transplantation; lipoprotein(a) is reduced [20], and hypercholesterolemia is easier to control [21]. Such changes were confirmed in our population: one year after transplantation there was a general improvement in cardiovascular risk factors including brachial blood pressure, lipids, and homocyst(e)ine levels.…”
Section: Discussionsupporting
confidence: 66%
“…There is frequently a reduction in blood pressure posttransplantation mirroring the central blood pressure regulatory role of the kidney, but also contributing is the increased use of vasoactive agents. Improvement in lipid parameters also follows restoration of normal renal function post-transplantation; lipoprotein(a) is reduced [20], and hypercholesterolemia is easier to control [21]. Such changes were confirmed in our population: one year after transplantation there was a general improvement in cardiovascular risk factors including brachial blood pressure, lipids, and homocyst(e)ine levels.…”
Section: Discussionsupporting
confidence: 66%
“…In contrast, mixed results regarding Lp(a) have been reported from cross sectional studies (163,169,174,185,(194)(195)(196)(197)(198)(199)(200)(201)(202)(203)(204). Notably, the decrease of Lp(a) in renal transplant patients was in dependent of the modality of immunosuppressive therapy (169,(184)(185)(186)(187)(188)(189)(190)(191), arguing against a contribution by an in flammatory component.…”
Section: Menopausementioning
confidence: 99%
“…The influence of renal transplantation on Lp(a) con centrations has also been investigated and prospective studies generally demonstrate a decrease of Lp(a) levels following kidney transplantation (169,(184)(185)(186)(187)(188)(189)(190)(191)(192)(193), although the followup period has been limited. In contrast, mixed results regarding Lp(a) have been reported from cross sectional studies (163,169,174,185,(194)(195)(196)(197)(198)(199)(200)(201)(202)(203)(204).…”
Section: Menopausementioning
confidence: 99%
“…Concerning Lp(a), prospective studies have shown that its concentration falls rapidly during the first weeks [9, 15, 16]and maintained normal values at 6 months [15, 16]and 1 year [17]following renal transplantation.…”
Section: Discussionmentioning
confidence: 99%